Influencing customer demand : an operations management approach - Hemmati, M.; Sajadieh, Mohsen S. (CRC Press, 2021)
"In today's competitive markets, considering the demand and the supply chain sides are crucial to keeping revenue and customer satisfaction maximized. Managing and planning demand play a vital role in the sustainability of a company. This is the first book to discuss managerial, mathematical, and the conceptual framework of influencing factors on demand along with accurate mathematical analysis to evaluate and raise revenue. The book provides an understanding of the key factors that influence buyer demand. It presents the mathematical relationship between the influencing factors and the demand functions. It discusses the methods used for influencing demand, how to measure demand dependence on factors such as price, quality, and inventory and it helps management improve alignment between supply and demand by affecting the levels and understanding the role within the SCM. This book is applicable for the professional, as well as for academia. It can help those working in SCM, Project Management, Production, Inventory Control, Scheduling, Engineering Management, Retail Management, and Operations Management"--